The mechanism of the hydrothermal alteration of cerium- and plutonium-doped zirconolite - Pöml, P.; Geisler, T.; Cobos-Sabaté, J.; Wiss, T.; Raison, P.; Schmid-Beurmann, P.; Deschanels, X.; Jégou, C.; Heimink, J.; Putnis, Andrew (2011)
A comprehensive study on the aqueous stability of Ce- and Pu-doped zirconolite has been performed. Four series of hydrothermal experiments were carried out with Ce-doped zirconolite powders: (1) a solution series (1 M HCl, 2 M NaCl, 1 M NaOH, 1 M NH3, pure H2O), (2) a temperature series (T = 100-300 °C), (3) a surface area-to-fluid volume ratio series, and (4) a series using different reactor materials (Teflon©, Ni, and Ag). In addition, experiments on 238Pu- and 239Pu- doped zirconolite ceramics in a 1 M HCl solution have been performed. The 238Pu-doped zirconolite had already accumulated significant radiation damage and was X-ray amorphous, while the 239Pu-doped zirconolite was still well-crystalline. The results of the different experimental series can be summarized as follows: (1) After 14 days the degree of alteration is insignificant for all solutions other than 1 M HCl, which was therefore used for all other experimental series; (2) TiO2 and m-ZrO2 replaced the zirconolite grains to varying degrees in the 1 M HCl solution, i.e., zirconolite dissolution is incongruent; (3) the degree of alteration increases only slightly with increasing temperature; (4) the alteration rate is independent on the surface to volume ratio; (5) Ag dissolved from the silver reactors dramatically increases the reaction rate, while Ni from the Ni reactors reduces the solubility of Ti and Zr in the HCl solution, indicating that background electrolytes have a strong effect on the alteration rate. From the experiment with the Pu-doped samples at 200 °C in a 1 M HCl solution it was found that the amorphous 238Pu-doped zirconolite was altered to a significantly greater extent than the crystalline counterparts. The results suggest a coupled dissolution-reprecipitation mechanism, which is discussed in detail.